2022
DOI: 10.1111/jcms.13335
|View full text |Cite
|
Sign up to set email alerts
|

How to Reflexively Decentre EU Foreign Policy: Dissonance and Contrapuntal Reconstruction in Migration, Religious and Neighbourhood Governance

Abstract: This article develops a timely new model for EU foreign policy by advancing the call for a ‘decentring agenda’, focused on the challenge of inclusive ‘reconstruction’. It does so by first staking out an ontological space at the intersection of empirical multiplexity and normative pluriversality. Within this space, it proposes an ethically informed methodological tool: the contrapuntal negotiation of dissonant perspectives on common governance challenges. It then suggests ways to reconstruct analytical and poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…By extending this concept to supply chains, organizations can collaborate with suppliers, distributors, and other stakeholders to establish ethical practices that transcend cultural and economic differences. For instance, consider a multinational corporation sourcing raw materials from different parts of the world [9]. By applying negotiation principles, they can work with suppliers to ensure fair pricing that accounts for local economic conditions while maintaining a commitment to fair wages and labor standards.…”
Section: Harmonizing Diplomacy and Theology: Strategies For Ethical S...mentioning
confidence: 99%
“…By extending this concept to supply chains, organizations can collaborate with suppliers, distributors, and other stakeholders to establish ethical practices that transcend cultural and economic differences. For instance, consider a multinational corporation sourcing raw materials from different parts of the world [9]. By applying negotiation principles, they can work with suppliers to ensure fair pricing that accounts for local economic conditions while maintaining a commitment to fair wages and labor standards.…”
Section: Harmonizing Diplomacy and Theology: Strategies For Ethical S...mentioning
confidence: 99%
“…If the EU is to truly own up to its vocation as a ‘post‐colonial power’, it needs to reflexively decentre its external relations (Fisher Onar and Nicolaidis, 2013; Nicolaidis and Fisher Onar, 2015; Wolff et al, 2022). Adopting a different approach to much critical analysis, we suggest that the kind of radical decentring implied here should not be a matter of simply pointing to the historical baggage in EU external policies (a matter beyond this article's remit).…”
Section: Conceptual Foundationsmentioning
confidence: 99%
“…Significant developments have been made to offer convinced researchers tools for how to go about decentring. In particular, Fisher Onar and Nicolaïdis (2013Nicolaïdis ( , 2021, Lecocq (2018, 2021), Huber and Paciello (2020) and Wolff et al (2022) have contributed to providing concrete steps, analytical frameworks and methodological tools to approach research on Europe and its role in the world in a more non-Eurocentric way. However, within the context of mainstream European (External Action) Studies, questions arise about the theoretical case for decentring (Dijkstra and Vanhoonacker 2017) and about the concrete contribution decentring can make to a scholarship that is mainly interested in Europe, the EU itself and its inner workings.…”
Section: Decentring: a Meta-theoretical Current Of Thinkingmentioning
confidence: 99%
“…As such, decentring can take various forms with different implications for scholarship. Imported from its counterpart in International Relations (IR), which calls for diversifying and decentring the study of global affairs (Tickner and Waever 2009;Nayak and Selbin 2010;Acharya 2014;Hurrell 2017;Tickner and Smith 2020), this debate also emerged in European scholarship, criticising Eurocentrism in its various forms (Hobson 2012;Sabaratnam 2013) and arguing for a 'Decentring Agenda' for EU External Action Studies, geared towards finding tools to overcome the identified Euro-, EU-and broader Western centrism in scholarship and practice (Fisher Onar andNicolaïdis 2013, 2021;Huber and Kamel 2018;Lecocq 2018, 2021;Huber and Paciello 2020;Wolff et al 2022;Zardo and Wolff 2022).…”
mentioning
confidence: 99%